Assessing Menstrual Cup Acceptability and Benefits in Uganda and Mozambique - Nyanteng, Kofi Kyeremateng; Mensah, Claudia Nyarko; Denning, Christine Garde (British Journal of Healthcare and Medical Research, 2022)
Background: Managing menstrual hygiene is a challenge among girls and women especially in low-income countries due to traditional beliefs, lack of knowledge and information on best hygienic practices, and limited access to appropriate and affordable menstrual hygiene products. An alternative to using sanitary pads or tampons for menstrual hygiene management, is the menstrual cup. CouldYou? a US-based non-profit is addressing the challenges of Menstrual Health Management of rural women and girls in Africa with the CouldYou? Cup, a menstrual cup. There was an intervention through this initiative in selected provinces in Mozambique and Uganda where women and girls received the menstrual cup. This study therefore examines the acceptability and benefits of the CouldYou? Cup in these countries. Methods: The menstrual hygiene intervention in Uganda and Mozambique covered the period August 2021 to January 2022, on a sample size of one hundred and fourty-two (142) teenagers and adults who received CouldYou? Cups (menstrual cups.) One hundred and seven (107) were from Mozambique and thirty-five (35) from Uganda. The study selected participants from the Nampula province in Mozambique and Kyakitanga, Seguku, and Zana provinces in Uganda. The study categorized the respondents into teenagers and adults with overall average age being nineteen (19) years. Age ranged between twelve (12) and fourty-three (43) years. Community-based participatory research (CBPR) tools were used to record views and elicit rich responses from the girls. Quantitative surveys were conducted using KoboCollect. The qualitative data, on the other hand, was collected through FGDs and KIIs using interview guides and semi-structured interviews. Findings: The study has revealed that participants use multiple products to address their menstrual needs in Uganda and Mozambique. Since the women and girls started using the menstrual cup, the menstrual cup has become a sustainable and safer substitute for unhygienic menstrual products including old clothes / rags and toilet rolls. The menstrual cup has an average of 91.5% acceptability rate in Mozambique and Uganda measured by the willingness of participants to use the product. Acceptability was 100% in Uganda and 88.8% in Mozambique based on the willingness of participants to use the menstrual cup. Measuring acceptability by the product adoption rate gives a 95.8% acceptability across all countries and 98.6% when acceptability is measured by the “like” for the cup. On the average, each participant used the cup for four (4) months. 58.5% depended on only the menstrual cup and 36.6% used the menstrual with sanitary pads, and 0.7% used the menstrual cup with tampons to manage their monthly menstrual needs. In-depth interviews showed that participants who could afford sanitary pads, preferred to use the menstrual cup as a substitute to cut down their recurring monthly expenditure on menstrual products. Participants described economic and convenience as advantages of using the menstrual cup. Purchasing sanitary products was an economic burden to the study participants. Expenditure on menstrual products varied significantly across both countries. Results from a paired sample test across both countries showed a significant decrease in participants monthly expenditure on menstrual products by 76.5%. Average monthly expenditure had (at the point of data dissemination) decreased by 81.9% in Mozambique and by 23.5% in Uganda. Conclusion: Findings from this study reflect that the menstrual cup is accepted and used widely as a substitute for sanitary pads. The economic advantage of the menstrual cup outweighs all other benefits.